Clustering of Palm Oil Production Results with K-Means Algorithm in West Aceh Regency - Sanusi; Ilham Juliwardi; Muhammad Ardiansyah; Nica Astrianda; Ana Elviajakfar (LPPM Politeknik Aceh Selatan, 2022)
The area and production of oil palm in West Aceh continues to experience a significant increase, because along with the expansion of oil palm plantations in the local area, it is very influential on employment and improving the economy of the community. This study aims to group the results of oil palm production and planted area by applying the data mining technique method with the K-Means Clustering algorithm. The data used in this study in the form of area and palm oil production results were obtained from the West Aceh catalog (BAPPEDA) and the Central Statistics Agency from 2005 to 2020 in 12 sub-districts of West Aceh Regency. The results of the study showed that the high cluster (cluster 1) contained 1 sub-district, namely Kaway XVI, the medium cluster (cluster 0) there were 7 sub-districts namely Bubon, Johan Pahlawan, Panten Reu, Samatiga, Sungai Mas, Woyla Barat, and Woyla Barat, while the cluster low (cluster 2), there are 4 sub-districts, namely Arongan Lambalek, Meureubo, Pante Ceureumen, and Woyla.